Pengaruh Model Pembelajaran REMAP STAD dalam Melatih Keterampilan Literasi Sains Peserta Didik - Ferry Irawan; Muh. Rafi'y; Dharma gyta Sari harahap (Indo-MathEdu Intellectuals Journal, 2023)
This study aims to determine the effectiveness of the STAD Remap learning model which can be used dynamically, as well as to facilitate students in a structured way to understand each p learning material which has very broad material derivations. Understanding broad material requires valid media. The research carried out is classified as a quasi experiment. The respondents in this research were science students at SMA Negeri 4 Malang. Data on scientific literacy skills is measured using essay questions that have been adapted to the achievement indicators of scientific literacy according to Gormally. The questions prepared are validated by expert validators before being carried out by students. Then a prerequisite test was carried out, namely the normality test and homogeneity test and finally the anacova one way test to find out the role of the STAD Remap learning model in improving students' scientific literacy skills